Using mathematical model to evaluate effects of green features on urban drainage - Ong, Allisa Yan Xin (Nanyang Technological University, 2023)
Urbanisation and climate change has drastically heightened the risk of inundation. Green infrastructures have emerged as a robust strategy to ensure the long-term sustainability of urban drainage systems for flood control. Previous low impact development (LID) studies have adopted various evaluation strategies to assess their effectiveness in flood risk mitigation and runoff treatment, primarily at a planning level. However, there is limited information regarding individual LID designs to produce better outcomes. The main objective of this study is to evaluate the effects of LID on urban drainage systems by assessing the technical-economic feasibility of different LID design parameters and implementation strategies against 2 crucial objectives of runoff management. First, a hypothetical residential development site was modelled using Storm Water Management Model (SWMM) to simulate peak runoff flow rates and total suspended solids (TSS) removal by the overall LID system. Second, the 50-year lifecycle cost (LCC) of the LIDs were estimated using STEP Life Cycle Cost Tool (LCCT) for subsequent cost benefit analysis. Third, brute force search optimisation was performed to achieve the optimal balance between cost of LIDs and (1) hydrologic performance or (2) water quality benefits. The results from this study indicate varying practicality of the investigated designs and strategies. These findings will help expand the research on cost-effective implementation of LIDs for urban runoff management, especially for development sites that have pre-defined allotment areas for LIDs.